DATA PROCESSING TRAINING USING MICROSOFT EXCEL FOR STUDENTS OF THE FACULTY OF AGRICULTURE, MALIKUSSALEH UNIVERSITY - Rusydi, Rachmawati; Mainisa, Mainisa; Mahdaliana, Mahdaliana; Hatta, Muhammad; Ayuzar, Eva; Salamah, Salamah (Universitas Muhammadiyah Aceh, 2023)
Data processing is part of the statistics used for drawing conclusions on the data analyzed using various statistical softwares. One of the softwares for simple data processing is Microsoft Excel. However, the use of Microsoft Excel for statistical analysis by students of the Agriculture Faculty, Malikussaleh University is not optimal compared to some other software. The purpose of this training activity is to provide data processing knowledge and skills to students of the Agriculture Faculty, Malikussaleh University using Microsoft Excel on data analysis. The community service activities were carried out at the Statistics Laboratory of the Agriculture Faculty, Malikussaleh University in March 2023. The method applied was training on data analysis through data analysis microsoft excel. Evaluation of community service activities was carried out through a survey using an online questionnaire on the Google form. Data processing training activities using Microsoft Excel for students of the Faculty of Agriculture, Malikussaleh University provided increased knowledge and skills. Students assessed that the use of Microsoft Excel in data processing was important and necessary in addition to other software. Furthermore, the training activities were considered very good, in terms of delivery, materials, and discussion time. Keywords: Data Processing; Microsoft Excel, Student, Agriculture